Greater Progression of Age-Related Aortic Stiffening in Adults with Poor Trunk Flexibility: A 5-Year Longitudinal Study - Gando, Yuko; Murakami, Haruka; Yamamoto, Kenta; Kawakami, Ryoko; Ohno, Harumi; Sawada, Susumu S.; Miyatake, Nobuyuki; Miyachi, Motohiko (Frontiers in Physiology, 2017)
Purpose: Having a low level of physical fitness, especially cardiorespiratory fitness, appears to accelerate age-related aortic stiffening. Whereas some studies have reported that trunk flexibility is a component of physical fitness, it is also negatively associated with arterial stiffening independent of cardiorespiratory fitness in cross-sectional studies. However, no long-term longitudinal study has determined whether poor trunk flexibility accelerates the progression of age-related aortic stiffening. We examined trunk flexibility and aortic stiffness progression in a 5-year longitudinal study. Methods and Results: A total of 305 apparently healthy men and women participated in this study (49.6±9.5 years of age). Trunk flexibility was measured by a sit-and-reach test. Aortic stiffness was assessed using carotid-femoral pulse wave velocity (cfPWV) at baseline and after 5 years. Analysis of covariance (ANCOVA) was used to assess the association of the annual rate of cfPWV across flexibility levels (low, middle, high). There were no significant differences in baseline cfPWV among the three groups (835±164, 853±140, 855±2.68 (cm/sec); P = 0.577). Annual ΔcfPWV was significantly higher in the low-flexibility group than in the high-flexibility group (P = 0.009). ANCOVA revealed an inverse relationship between flexibility level and annual ΔcfPWV (14.41±2.73, 9.79±2.59, 2.62±2.68 cm/sec/year; P for trend = 0.011). Multiple regression analysis revealed that baseline sit and reach (β = -0.12, -0.70 to -0.01) was independent correlates of ΔcfPWV following adjustment for baseline peak oxygen uptake, age, sex, body fat, heart rate, and cfPWV. The 5-year change in cfPWV was not significantly correlated with 5-year change in sit-and-reach performance (P = 0.859). Conclusion: Poor trunk flexibility is associated with greater progression of age-related aortic stiffening in healthy adults. However, we failed to confirm a significant association between 5-year change in aortic stiffness and 5-year change in trunk flexibility. The association between increased age-related increase in aortic stiffness and deterioration in flexibility due to age may require observation for more than 5 years.